THE INFLUENCE OF SERVICE QUALITY AND IMPLEMENTATION OF PUBLIC RELATIONS CUSTOMER SATISFACTION ON SERVICE RECIPIENT SATISFACTION AT THE YOGYAKARTA COURT OFFICE - Anna Sulistyawati; Rita Listiyanti (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
The objectives of this research include: (1) To determine the magnitude of the influence of information quality on the satisfaction of people receiving services at the Yogyakarta Religious Court Office. (2) To determine the magnitude of the influence of the implementation of Public Relations consumer satisfaction on the satisfaction of the people receiving services at the Yogyakarta Religious Court Office. (3) To determine the magnitude of the influence of the implementation of consumer satisfaction, public relations, consumer satisfaction and service quality on the satisfaction of the community receiving services at the Yogyakarta Religious Court Office. This type of research is quantitative research. The population in this study were all service recipients at the Yogyakarta Religious Court Office. The sampling technique used simple random sampling technique with a sample size of 100 people. The data collection technique in this research uses a questionnaire. The data analysis technique uses multiple regression analysis. Based on the findings and data analysis carried out in the previous chapter, the following conclusions can be drawn: (1) The implementation of consumer satisfaction public relations has a positive effect on the satisfaction of the people receiving services at the Yogyakarta Religious Court Office. (2) Service quality has a positive effect on the satisfaction of the people receiving services at the Yogyakarta Religious Court Office. (3) The quality of information and the quality of service have a positive effect on the satisfaction of the people receiving services at the Yogyakarta Religious Court Office. The variables quality of information and quality of service influence public satisfaction by 30.9%, while the remaining 69.1% is influenced by other variables outside the research.